FORECAST OF THE EXPORT OF FRESH STRAWBERRIES FROM THE REPUBLIC OF SERBIA USING THE ARIMA MODEL - Zdravković, Vladimir D.; Janković Šoja, Svjetlana D.; Vučković, Dejana J. (Journal of Agricultural Sciences (Belgrade), 2026)
Regarding the export of fruit intended for fresh consumption, fresh strawberries are among the leading export products of the Republic of Serbia. The main export market for fresh strawberries is the Russian Federation, where an average of 8,447 tonnes of strawberries were exported in the period from 2016 to 2021, which is about 89% of the total export. In the past five years, the export of strawberries from the Republic of Serbia has halved, as a result of the loss of the dominant Russian Federation market. If this trend continues, the Republic of Serbia will lose $10.3 million a year in foreign trade, while the drop in exports will increase supply on the domestic market, leading to a drop in prices and negatively affecting the profitability of this production. The aim of this paper is to find a model that best describes future trends in the export of this fruit using the ARIMA model. The long-term monitoring of exports by the Statistical Office of the Republic of Serbia enables the prediction of this parameter in the coming years. The analysis established that, for the period from 2001 to 2022, the ARIMA (3, 1, 6) model is adequate for forecasting future trends in the export of this fruit. Forecasts suggest that exports of fresh strawberries from the Republic of Serbia will continue to decline in the coming years.
Keywords: ARIMA models; strawberry export; forecasting; Box-Jenkins modeling strategy; Republic of Serbia